2021
DOI: 10.3390/molecules26247686
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Single and Binary Mixture of Brilliant Green and Rhodamine B Dyes by Zinc Sulfide Quantum Dots

Abstract: We present the preparation of octadecylamine-capped ZnS quantum dots from bis(morpholinyldithiocarbamato)Zn(II) complex. The complex was thermolyzed at 130 °C in octadecylamine at different times, to study the effect of reaction time on the morphological and photocatalytic properties of the ZnS quantum dots. Powder X-ray diffraction patterns confirmed a hexagonal wurtzite crystalline phase of ZnS, while HRTEM images showed particle sizes of about 1–3 nm, and energy band gaps of 3.68 eV (ZnS–1), 3.87 eV (ZnS–2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Ragupathy et al reported that Sn-doped ZnO loaded CSAC (Sn–ZnO/CSAC) NPs photocatalytically degrades 96.52% BG in 120 min . Similarly, octadecylamine-capped ZnS quantum dots were reported to degrade 94.61% BG in 180 min . Our work involves the synthesis of Fe–ZnO that photocatalytically degrades BG up to 99% in just 30 min.…”
Section: Introductionmentioning
confidence: 72%
“…Ragupathy et al reported that Sn-doped ZnO loaded CSAC (Sn–ZnO/CSAC) NPs photocatalytically degrades 96.52% BG in 120 min . Similarly, octadecylamine-capped ZnS quantum dots were reported to degrade 94.61% BG in 180 min . Our work involves the synthesis of Fe–ZnO that photocatalytically degrades BG up to 99% in just 30 min.…”
Section: Introductionmentioning
confidence: 72%
“…All the diffraction peaks of ZnS nanoparticles correspond with the standard values of hexagonal wurtzite zinc sulfide (JCPDS card no. 39–1363). , The differences in the diffraction patterns and the number of peaks could be ascribed to the different capping agents used to prepare the nanoparticles. The broad diffraction peaks observed could be attributed to the small particle sizes of the as-prepared zinc sulfide nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the incomplete recovery of catalysts, material agglomeration or accumulation of a small amount of the RhB on the surface of catalysts. 6,18,23 The XRD results of Z-L-ZnS-180 before and after cyclic experiments are shown in Fig. 15(b).…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Among them, photocatalytic technology has been evaluated as an ideal method with huge economic and social benefits due to its advantages of low energy consumption, high efficiency, and being environment friendly. 6,7 The key problem of this method is the selection of suitable photocatalysts. Currently, scholars are struggling to explore efficient photocatalysts, including oxides, 8 sulfides, 9 carbides, 10 and metal-organic frameworks (MOFs).…”
Section: Introductionmentioning
confidence: 99%